Causes and Forms of Cyberbullying among Teenagers in Indonesian Urban Areas: Cases of Jakarta, Bandung and Surabaya - Amanatin, Elsa Lutmilarita; Sekarningrum, Bintarsih (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2023)
The development of digitalization has had an impact on the increasing cases of cyberbullying among Indonesian youth, especially in urban areas such as Jakarta, Surabaya, and Bandung. This article finds out why teenagers in urban areas are rampant in carrying out cyberbullying behavior. The existing studies were examined to map the causes and forms of cyberbullying experienced by teenagers in the three cities by applying inclusion and exclusion criteria. Employing Anthony Giddens structuration theory, this article reveals that cyberbullying among urban teenagers is the impact of the relationship between agents and structures that shape social reality. In Jakarta, cyberbullying has emerged as a result of the lack of social support from peers and the low emotional intelligence that teenagers have. In Surabaya, cyberbullying arose as a result of lack of self-control and parental evaluation mediation, low self-esteem, and a strong desire for self-recognition in order to show their power. In Bandung, cyberbullying arose as a result of the anonymity and authoritarian pattern of parental care.